PERUBAHAN POLA KOMUNIKASI MASYARAKAT KOMUNITAS SUKU SASAK DUSUN SADE (Suatu Studi Etnografi di Desa Wisata Komunitas Suku Sasak Dusun Sade Lombok Tengah) - , Sarga Surya Data ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research on \"Changes in Public Communication Patterns Sasak Tribe in Sade Village (An Ethnographic Study of Tourism Sade Village, Village Rembitan, Pujut District, Central Lombok, West Nusa Tenggara)\". Under the supervisor of: Dr. Phil. Ana Nadhya Abrar, MES, and Muhammad Sulhan, S.IP., M.Si Sade Sasak village community is a community that is deemed to be strong to survive until now held the original culture of the Sasak Lombok. However, in the progress of society Sade was not separated from the influence of modernization as a result was unable to escape from the building, which offers a clattering rupiahs as well as the occurrence of intense interaction with the surrounding communities and tourists, the pull of the outside world for a given sample the modern world causes people to change Sade. these changes have an impact on patterns of communication that has been running for so long. for that these changes are very interesting to study. This study investigates and identifies how the Pattern Change Communication Community in Sasak Sade community. The results showed that the communication process that occurs in Sade society has undergone changes, including patriarchal culture that began to loose in Sade society, was seen in the equal rights to education and employment for women and men in Sade society. Parent mainset who has changed where the orientation of living far ahead, visible from parents who begin to think of their children's education, as well as freeing the children to determine their own mate. Unlike in the past which must be paired. Economic opportunities for all Sade communities is not only owned by the leaders or elders community, but all the people of Sade village. One's of symbol wealth is no longer seen from the number of rice owned but owned facilities such as motor vehicles and home appliances. Changes in lifestyle of the traditional society into a modern society and consumptive. Understanding of the young generation of the meaning of a symbol of religious rituals and customs began to decrease, adherence to norms, politeness, taboo eroded. Completeness of religious ceremonies and is being replaced with modern equipment, traditional ceremonies and commodified art as a tourist attraction that has a sale value. These changes can be seen happening in the environment kinship, government, education, economy, religion and customs. These changes are caused by three main factors: first social interaction, social interaction with tourists or people outside the community Sade through direct or indirect communication with the electronic media with a wide variety of cultural backgrounds and more modern. Experience that they can later be adopted in their daily lives. The second factor, the opening of economic opportunities that allow each community Sade Hamlet able to adjust their lives to a more modern, and the third factor is the formal education, formal education is a means to transform modern knowledge, so that they learn to apply it in their daily lives.